Pendekatan Multikultural untuk Meningkatkan Toleransi Peserta Didik - Katoda, Abigain; Kristiani, Kristiani (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
Indonesia, recognized as one of the most culturally diverse countries globally, presents an extraordinary array of linguistic, ethnic, cultural, religious and other variations. Nonetheless, there are still multicultural tensions stemming from differences in culture, religion and other sociocultural dimensions, suggesting that the pursuit of multicultural education in Indonesia has not produced optimal and equitable results. Therefore, it is imperative to adopt a multicultural framework that fosters values that can be achieved by learners and a society characterized by tolerance and peace. This research utilizes a qualitative methodology with a focus on a library study, which aims to collect diverse literary sources related to the idea of multicultural education and its role in fostering attitudes of tolerance. By promoting multicultural principles, enhancing inclusive curricula, and providing appropriate guidance from educators, this approach can profoundly enhance students' capacity for tolerance.